BUTIK SAMPAH MINI-WORKSHOP UNTUK MENGURANGI LIMBAH PAKAIAN MENJADI KERAJINAN TAS - Vidyana Arsanti; Fitria Nuraini Sekarsih (Servirisma, 2022)
Garbage is a major problem in urban areas that has not been fully resolved. Along with an increasingly consumptive lifestyle, there will be an increase in the amount of waste. Another thing that drives the increase in the amount of waste in urban areas is changing trend rapidly of clothing, which contributes to the increase in the amount of clothing waste. This condition prompted the Amikom team together with the Bener Faskel, Head of Bener Village, the BERAMAL (Environmentally Friendly) management, the Head of the Citizens Association and the Chair of the Pokja IV PKK to make waste management innovations. The purpose of this activity is to solve the problem of clothing waste to improving the quality of the environment. The result of this community activity is a training activity to convert clothing waste into crochet bags and wallet. The output of this community activity is increasing the skills of the waste bank administrators to turn clothing waste into more useful goods. The conclusion of this activity: (1) Garbage from non-natural fibers is anorganic waste that cannot be collected in the waste bank. There needs to be a recycling activity so that the waste can be more useful, (2) One of the recycling activities from clothing waste management is derivative products such as crochet bags and wallets (3) Mini workshops will run effectively for 2 hours because participants have been provided with materials by video tutorials, and (4) this mini workshop makes the value of clothing waste more useful.